The art of speaking - Aquino, Avelino (Manila, 2006)
This text has been written especially for college students, with particular concentration on their specific speech needs and weaknesses. Throughout its preparation and presentation , the objective has ben foremost: to present, in the most simplified form possible, the fundamental features of speech so that the college students may develop their desire to become effective communicators.
Keywords: Speech